A simple method for estimating the effective detection distance of camera traps. Issue 2 (9th September 2016) - Hofmeester, Tim R.; Rowcliffe, J. Marcus; Jansen, Patrick A.
Abstract: Estimates of animal abundance are essential for understanding animal ecology. Camera traps can be used to estimate the abundance of terrestrial mammals, including elusive species, provided that the sensitivity of the sensor, estimated as the effective detection distance (EDD), is quantified. Here, we show how the EDD can be inferred directly from camera trap images by placing markers at known distances along the midline of the camera field of view, and then fitting distance‐sampling functions to the frequency of animal passage between markers. EDD estimates derived from simulated passages using binned detection distances approximated those obtained from continuous detection distance measurements if at least five intervals were used over the maximum detection distance. A field test of the method in two forest types with contrasting vegetation density, with five markers at 2.5 m intervals, produced credible EDD estimates for 13 forest‐dwelling mammals. EDD estimates were positively correlated with species body mass, and were shorter for the denser vegetation, as expected. Our findings suggest that this simple method can produce reliable estimates of EDD. These estimates can be used to correct photographic capture rates for difference in sampling effort resulting from differences in sensor sensitivity between species and habitats. Simplifying the estimation of EDD will result in less biased indices of relative abundance, and will also facilitate the use of camera trap data for estimating animal density. Abstract : We present a simple method to estimate effective detection distance of camera traps, which will enable camera trap data to be corrected for biases in detection probability between species and habitats. The method uses a line of markers in the centre of the camera view, which enables rapid estimation of trigger distances of animals passing the camera view using images taken by the camera trap. These distance estimates can be used to estimate effective detection distance using distance‐sampling techniques.